2017
DOI: 10.1134/s1560354717080056
|View full text |Cite
|
Sign up to set email alerts
|

The Chaplygin Sleigh with Parametric Excitation: Chaotic Dynamics and Nonholonomic Acceleration

Abstract: This paper is concerned with the Chaplygin sleigh with timevarying mass distribution (parametric excitation). The focus is on the case where excitation is induced by a material point that executes periodic oscillations in a direction transverse to the plane of the knife edge of the sleigh. In this case, the problem reduces to investigating a reduced system of two first-order equations with periodic coefficients, which is similar to various nonlinear parametric oscillators. Depending on the parameters in the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 60 publications
(66 reference statements)
2
34
0
3
Order By: Relevance
“…В частности, его изучение является одной из задач управления различными роботами. Недавно был получен ряд новых результатов в связи с ускорением саней Чаплыгина (являющихся простейшим примером колёсного робота), которое достигается с помощью изменения положения центра масс или гиростатического момента [1][2][3].…”
Section: механикаunclassified
“…В частности, его изучение является одной из задач управления различными роботами. Недавно был получен ряд новых результатов в связи с ускорением саней Чаплыгина (являющихся простейшим примером колёсного робота), которое достигается с помощью изменения положения центра масс или гиростатического момента [1][2][3].…”
Section: механикаunclassified
“…Various generalizations of the problem of the Chaplygin sleigh were considered by many authors [20,21,22,23,24,25,26,27,28]. In particular, attention was given to problems of the motion of the sleigh in the presence of periodic impulse impacts [20,21], with periodic switchovers of the nonholonomic constraint to different locations [23,24], and with periodic transfers of the massive load placed on the sleigh [25,26]. Analysis was also made of the motion of the sleigh under the action of random forces which model a fluctuating continuous medium [28], when, according to the authors, the motion resembles random walks of bacterial cells with a diffusion component.…”
Section: Introductionmentioning
confidence: 99%
“…In [25], general equations are formulated which describe the motion of the Chaplygin sleigh with a given periodic transfer of several internal point masses relative to the platform. It is shown that, depending on the parameters, the system exhibits different types of motions, including those corresponding to strange attrac-tors, with which chaotic (diffusion) trajectories of the sleigh on a plane are associated.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose that n material points P (i) , i = 1, .., n move on the platform in a prescribed manner. In this case the kinetic energy of the entire system can be represented in the following form [3]:…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Starting with [12], strange attractors of different nature [6,30,5] are detected in nonholonomic systems. A strange attractor for the Chaplygin sleigh with a material point, which executes periodic oscillations in the direction transverse to the plane of the knife edge, is found in [1,3].…”
Section: Introductionmentioning
confidence: 99%